Evaluating the Effectiveness of Educational Intervention on ICU Nurses’ Knowledge of Delirium: A Quasi-Experimental Approach - Jamal Qaddumi; Khaled Awawdi; Mahdi Tarabeih (Nursing Reports, 2025)
Background and Objective: Delirium, a prevalent neurocognitive disorder, frequently affects critically ill patients hospitalized in intensive care units (ICUs), leading to increased mortality, prolonged hospital stays, and higher healthcare costs. This quasi-experimental study assessed the effect of an educational program relating to ICU nurses’ knowledge of delirium in a university hospital in Nablus, Palestinian Authority. Methods: A pre-test–post-test design was employed, utilizing a 25-item questionnaire for 114 ICU nurses. The educational intervention included a presentation on delirium, the distribution of educational materials, and follow-up video sessions. Our study aim was to evaluate nurses’ understanding of ICU delirium and the impact of the educational program on their ability to identify and evaluate the delirium. Results: Pre-intervention assessments indicated limited awareness among nurses regarding delirium diagnosis and management tools, i.e., the Confusion Assessment Method for the ICU (CAM-ICU) and the Intensive Care Delirium Screening Checklist. Post-intervention results showed a significant improvement in knowledge; median scores increased from 6 (range: 3–13) to 15 (range: 12–20) (p < 0.001). Nurses also reported greater confidence in identifying and managing delirium, and 50% found CAM-ICU easy to use. However, knowledge gaps remained concerning mixed delirium types and modifiable risk factors. Conclusions: Continuous educational programs are essential for ensuring long-term knowledge retention. We recommend integrating routine delirium education with hospital policies and emphasizing the use of delirium assessment tools during each shift. Findings show that targeted education can enhance ICU nurses’ competencies and thereby improve patient outcomes through more effective delirium management.